Penerapan Metode Ceramah Dan Diskusi Kelompok Dalam Upaya Meningkatkan Pemahaman Siswa Mata Pelajaran Fiqih Di MTS Al-Mahrus - Sindy Lestari; Nur Rizki; Nur Azizah (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2023)
Learning is a process activity carried out by individuals with the aim of obtaining a change in behavior as a form of experience in interaction with the environment. This research was conducted with the aim of improving the learning outcomes of fiqh subjects at MTs Al-Mahrus through direct implementation of the lecture method and group discussions. The subjects in this study were teachers who applied discussion and lecture learning models. The research method used is qualitative and observation. The data generated from this study were sourced from fiqh subject teachers who were interviewed and observations made at MTs Al-Mahrus. The data analysis techniques used in this study are data reduction, data presentation, verification and conclusions.